Studi terhadap Polemik antara Larangan dan Pembolehan Penulisan Hadis - Wahyudi, Rizki Imam (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2023)
Hadith, which is the second source of Islamic law, apart from functioning to explain the Qur'an, also serves to reinforce the laws of the Koran and serves to establish laws that are not found in the Koran. There are two contradictory hadiths related to the writing of hadith: the hadith which prohibits and the hadith which encourages the writing of hadith. The orders to pray, pay zakat, and perform Hajj are only mentioned in general. The Qur'an does not explain the number of cycles and the ways of performing the prayers, does not specify the nisabs of zakat, and also does not explain the ways of performing the pilgrimage. But all of that has been explained in detail and interpreted as broadly as possible by hadith. This research is a study that uses the literature review method which aims to discuss the polemic between the prohibition and permissibility of the use of hadith. Seeing the importance of the position of the hadith, this paper wants to discuss the condition of the hadith at the time of the Prophet and his companions, which is the most important phase of the history of hadith. This discussion includes the understanding of hadith and sunnah, how friends receive hadith from the Prophet, discussions about the prohibitions and recommendations for writing hadith, and the attitude of friends towards the transmission of hadith. The books used are the opinions of previous scholars and authors, and the journals used are sourced from updated journals.